Delivering mobile eye care to underserved communities while providing training in ophthalmology to medical students: experience of the Guerrilla Eye Service - Williams AM (Dove Medical Press, 2019)
Andrew M Williams,* Benjamin Botsford,* Peter Mortensen, Daniel Park, Evan L Waxman Department of Ophthalmology, University of Pittsburgh Medical Center, Pittsburgh, PA, USA *These authors contributed equally to this work Objective: The objective of the study was to characterize the population served by the student-led Guerrilla Eye Service (GES), a mobile outreach program that delivers comprehensive ophthalmic care to underserved communities in the greater Pittsburgh area.Patients and methods: Patients attending GES missions at a single urban free clinic from 2012 through 2017 were included in this retrospective case series. All patients underwent a comprehensive eye examination at no cost, with referral to a university eye clinic if necessary. Demographic characteristics, past ocular history, reasons for attendance, and ophthalmic diagnoses were recorded. Attendance rates and treatment outcomes of patients referred to the university eye clinic were also reviewed.Results: We reviewed records of 360 GES patients (mean age 43 years, age range 1–79 years; 56% [200] male; 37% [133] non-English speakers). The most common reasons for attending were blurry vision (28% [101]), need for new glasses (22% [80]), and referral for a diabetic eye exam (18% [63]). The most common diagnosis made was refractive error (59% [214]), and vouchers for free spectacles were provided. One-third of diabetic patients had retinopathy (32% [38]). Glaucoma suspect (11% [40]), narrow angles (4% [13]), treatment-requiring diabetic eye disease (4% [14]), and visually-significant cataract (3% [11]) were diagnoses that most often prompted referral to the university clinic. In all, 114 patients were referred (32%), of whom 82 (72%) attended the follow-up visit. Other patients continued to receive longitudinal care through GES.Conclusion: Medical student-led outreach programs under the supervision of an attending ophthalmologist can deliver regular eye care to underserved communities while providing referrals to a university clinic for those with advanced disease. Keywords: vision health, public health, mobile medical care, eye care, education, community engagement